Porcine placental immunoexpression of vascular endothelial growth factor, placenta growth factor, Flt-1 and Flk-1 - Sanchis, Eva Gabriela (2015)
Porcine embryo mortalities cause economic losses. Development of the placental vascular bed is required for successful gestation and postnatal survival. We studied the temporal and spatial distributions of vascular endothelial growth factor (VEGF), placenta growth factor (PlGF) and their receptors, Flt-1 and Flk-1. We used crossbred swine placental tissues from 30, 60, 80, 90 and 114 (term) days of gestation. Both VEGF and PlGF were present during gestation. At early pregnancy and at term, VEGF probably acts through Flt-1; during intermediate periods, its function is mediated by Flk-1. By day 90, factors other than members of VEGF family appear to be involved.